Estudo sobre os processos avaliativos e a promoção escolar dos estudantes com deficiência - Silva, Lauriceia Tomaz da (2012)
At the current moment of Brazilian education. The issue of assessment practices experienced by students with disability, is still underexplored. Especially in relation to these concepts on their own educational experience. Within this reality, we developed a study that focuses on studying the relation between evaluation and flow of the students with disabilities, hearing reports of 14 students with disability, registered in high school from the Pernambuco state at Cabo de Santo Agostinho. The study is based on the constitutional principle that education is a subjective right, then the person with disabilities is a subject of law, and inclusive education constitutes a means to create opportunities for all to quality education, respecting the rhythms of development of each student. So we must to characterize and analyze the students flow with disabilities in the school; identify evaluative practices undertaken by teachers and applied to students with disabilities, and to relate the evaluation practices and student flow experienced by these students. The methodology used is the qualitative research and to analyze the data, we use the principles of inclusion and Cultural Studies. The results obtained from the subjects' statements indicate that despite the educational politics from Pernambuco point to an inclusive perspective of evaluation, in practice, the evaluation process presents a exclusive model yet. T at first it happens informally, to be established value judgments about the subject, after, formally, to be selected and classified the subjects, it s a relation of unilateral power, which sustains the teacher's authority over the academic life students. These evaluative practices hamper the flow of school students with disabilities, and are in addition to other factors present in the educational process, including the absence, in most cases, interaction between teacher and student with disabilities, the lake of comprehension or ignorance about the need to establish a practice of valuing differences. So points of order evaluative, educational and attitudinal barriers to overcome the school flow of people with disabilities in the context of a process to a good quality education for all.